Sovereignty as a Social Issue: The case of Inuit Nunangat. - Vardy, Mark (Arctic Portal, 2011)
Young researcher Mark Vardy, Queen’s University, Canada, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.